Donald S. Dawson papers - Dawson, Donald S., 1908-2005.; Lowenthal, Max, 1888-1971.
Correspondence, presidential campaign materials, and other papers. Correspondence is primarily with or about Harry S. Truman following his presidency. Also includes material relating to William McKinley Rigdon, Richard M. Nixon, Committee Against Socialist Housing, and the presidential campaigns of 1964 and 1968. Includes a photocopy of Max Lowenthal's 1948 diary.
Lawyer and government official.
Collection material in English.
Keywords: Nixon, Richard M. -- 1913-1994.; Rigdon, William McKinley, -- 1904-; Truman, Harry S., -- 1884-1972.; Truman, Harry S., -- 1884-1972 -- Correspondence; Committee Against Socialist Housing; Elections -- United States -- 1964.; Elections -- United States -- 1968.; Public housing -- United States; United States -- Politics and government -- 1945-1989.; Lawyers; Public officials